Self-portrait as your traitor - Millman, Debbie; Scher, Paula; Taylor, Brent (Cincinnati, Ohio HOW Books, 2013)
Debbie Millman has demonstrated her ability to combine thoughts about design and everyday life with her own obsessive hand drawn typography, creating a new form of visual poetry. She has invented a 21st century illuminated manuscript. -- from the introduction by Paula Scher.
Part of the Asia Pacific Design Library.
En. Muhd Norizam B. Jamian/norizam@ukm.edu.my/016-6889152/FSSK/Pusat Pengajian Bahasa, Kesusasteraan dan Kebudayaan Melayu/Serantau Makmur/KLBF2014/syila/cip/30.5.2014
Keywords: Visual poetry, American; Design -- Psychological aspects -- Pictorial works; Graphic design (Typography) -- Pictorial works; Visual communication in art; Graphic arts